(untitled) (American Journal of Islam and Society, 2008)
On September 11th, 2008, while countless American flags whipped in the wind and the television and radio waves were dominated by remembrances, recordings, and stories about the terror attacks of seven years ago, I attended the funeral of ImamW.D.Mohammed (may God be pleased with him). Forme, it was a somber day, but I found myselfmostly lost in thought: about African-American Muslim communities, about the challenges ahead in American Muslim institution-building, and about the future of Islam in America. If you don’t know who ImamWDMwas, you should look him up. The Sufis say: “The true sage belongs to his era.” And of the many gifts given to ImamWDM by God, perhaps the most obvious and beneficial one was the Imam’s profound understanding of the principles of religion, and his adeptness at intelligently applying those Islamic principles in a socially and culturally appropriate manner befitting the everyday lives of his North American followers. While carefully respecting sound, traditional jurisprudential methodologies of the Islamic religion, and the collective religious history and time-honored scholarship of classical Islam, he promulgated creative ideas and dynamic teachings across many domains of human endeavor, including theology, law, spirituality and even ethics and aesthetics, that together articulated a vision for a quintessentially “American Muslim” cultural identity. And he did all of this before anyone else, with quiet strength and unending humility – a true sage indeed ...